2018
DOI: 10.3390/nu10020125
|View full text |Cite
|
Sign up to set email alerts
|

Interrupting Prolonged Sitting with Regular Activity Breaks does not Acutely Influence Appetite: A Randomised Controlled Trial

Abstract: Regular activity breaks increase energy expenditure; however, this may promote compensatory eating behaviour. The present study compared the effects of regular activity breaks and prolonged sitting on appetite. In a randomised, cross-over trial, 36 healthy adults (BMI (Body Mass Index) 23.9 kg/m2 (S.D. = 3.9)) completed four, two-day interventions: two with prolonged sitting (SIT), and two with sitting and 2 min of walking every 30 min (RAB). Standardized meals were provided throughout the intervention, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Improved mood, when prolonged sitting is interrupted with PA breaks, is in line with previous literature [8,14] and may have important implications for the mental wellbeing of this population. Hunger on the other hand was unaffected by PA breaks, which could be beneficial in the management of overweight and obesity, and is in line with previous studies that reported unaffected appetite and ad libitum food intake when prolonged sitting is interrupted [53,54]. With these observations, it is important to emphasize that we standardized the activities during the sitting period.…”
Section: Cognitive Outcome Timesupporting
confidence: 87%
“…Improved mood, when prolonged sitting is interrupted with PA breaks, is in line with previous literature [8,14] and may have important implications for the mental wellbeing of this population. Hunger on the other hand was unaffected by PA breaks, which could be beneficial in the management of overweight and obesity, and is in line with previous studies that reported unaffected appetite and ad libitum food intake when prolonged sitting is interrupted [53,54]. With these observations, it is important to emphasize that we standardized the activities during the sitting period.…”
Section: Cognitive Outcome Timesupporting
confidence: 87%
“…Although perceptions of overall appetite were suppressed in response to hourly high-intensity physical activity breaks, there was no subsequent effect on ad libitum energy intake. This is synonymous with previous research evaluating 2-min light and moderate-intensity walking breaks every 20 min (13) and 2-min moderate-intensity walking breaks every 30 min (34). The present study extends these findings by demonstrating that high-intensity physical activity breaks also do not result in an acute compensatory increase in subsequent energy intake.…”
Section: Physical Activity Breaks Reduce Appetitesupporting
confidence: 90%
“…Similar to the present study, the moderate-intensity physical activity breaks in the study by Holmstrup, Fairchild, Keslacy, Weinstock, Kanaley ( 10 ) did not affect subjective appetite AUC over a single day in comparison to prolonged sitting without physical activity. Other research has reported no changes in appetite in non-overweight adults who engaged in 2-min light or moderate-intensity walking bouts every 20 min over 5 h ( 13 ) or 2-min moderate-intensity walking breaks every 30 min over a 2-day period ( 34 ). It thus appears that regular physical activity breaks suppress appetite over a single day compared with continuous exercise in participants with obesity and normal weight status but not when compared to prolonged sitting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was not originally designed to investigate the effects of breaking prolonged sitting on eating behavior, and so appetite-related measures were not assessed. Eating behavior has been reported to be unaffected by breaking sitting in young lean individuals (16,40), although this may be partly explained by the previously discussed lack of effect on gut hormone responses in some of these studies (16). Therefore, further research in this population is required to determine whether eating behavior and ad libitum energy intake would be altered by the changes to gut hormones observed in the current study.…”
Section: Discussionmentioning
confidence: 84%